Pemberdayaan UMKM Melalui Wakaf Hak Kekayaan Intelektual (HKI) Tinjauan Maqoshid Syariah - Maghfiroh, Saodatul (ITB AAS INDONESIA Surakarta, 2023)
This study describes a model of community empowerment by integrating MSMEs and nadzirs in using IPR waqf funds. Considering that MSMEs have a fairly central economic base and can be said to be the saviors of national economic development, support is required, especially in access to capital because internal capital is still a major problem for MSMEs to overcome. In the present. A conceptual model or framework is provided as part of the qualitative research methodology, and secondary data from systematic literature reviews, academic papers, and survey findings are utilized as data sources. IPR is considered one of the haqq maliyyah (property rights) in Islamic law that is legally protected in order to be waqf, specifically waqf in the form of moveable things other than money. The more royalties that are donated, the more money is gathered to be used as capital assistance for MSMEs so that more and more businesses can be run by the community. In addition, it can also create a healthy economic cycle, open up new jobs, lower unemployment, and speed up the economy. so that it may aid the neighborhood in meeting its everyday requirements, particularly its dharuriyah demands. For MSMEs to operate at their best, additional strategic actions must be made in addition to granting them access to financing. These actions include offering training and repair skills, business advising, enhancing product quality, markets, business networks, and technology